Impact of Artificial Intelligence on Fraud Detection in Retail Banking Products - Ramana, S. Venkata; Katta, Ashok Kumar; Rao, P Subba; Rao, S. Sivasankara; Raja, Rachagundla (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Artificial intelligence (AI), now and again called machine insight is a reenactment of human knowledge in machines. It is the insight displayed by machines, rather than the regular information showed by people Artificial Intelligence is a quick creating innovation across the world. The financial area is becoming one of the main adopters of man-made consciousness. Man-made thinking is communicated to be information by machines. Financial trades of the banks are inspected for learning, decisive reasoning, and choice creation with automated thinking, and by using tremendous data, advanced examination joined with AI estimations. The paper is connected to focusing on the impact of Artificial Intelligence (AI) in the n monetary region in India and the challenges looked by the monetary region in completing Artificial Intelligence. The mark of the survey is to examine the benefits of Artificial Intelligence in the monetary region in India.